Control of PD-L1 expression in CLL-cells by stromal triggering of the Notch-c-Myc-EZH2 oncogenic signaling axis - Böttcher, Martin; Bruns, Heiko; Völkl, Simon; Lu, Junyan; Chartomatsidou, Elisavet; Papakonstantinou, Nikos; Mentz, Kristin; Büttner-Herold, Maike; Zenz, Thorsten; Herling, Marco; Huber, Wolfgang; Ghia, Paolo; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Chronic lymphocytic leukemia (CLL) is the most common leukemia in adults. Emerging data suggest that CLL-cells efficiently evade immunosurveillance. T-cell deficiencies in CLL include immuno(metabolic) exhaustion that is achieved by inhibitory molecules, with programmed cell death 1/programmed cell death ligand 1 (PD-L1) signaling emerging as a major underlying mechanism. Moreover, CLL-cells are characterized by a close and recurrent interaction with their stromal niches in the bone marrow and lymph nodes. Here, they receive nurturing signals within a well-protected environment. We could previously show that the interaction of CLL-cells with stroma leads to c-Myc activation that is followed by metabolic adaptations. Recent data indicate that c-Myc also controls expression of the immune checkpoint molecule PD-L1. Therefore, we sought out to determine the role of stromal contact for the CLL-cells' PD-L1 expression and thus their immuno-evasive phenotype.
CRIS-Team WoS Importer:2021-05-21